Hormones regulate the flowering process in saffron differently depending on the developmental stage - Singh, Deepika; Sharma, Sahiba; Jose-Santhi, Joel; Kalia, Diksha; Singh, Rajesh Kumar (Frontiers in Plant Science, 2023)
Flowering in saffron is a highly complex process regulated by the synchronized action of environmental cues and endogenous signals. Hormonal regulation of flowering is a very important process controlling flowering in several plants, but it has not been studied in saffron. Flowering in saffron is a continual process completed in months with distinct developmental phases, mainly divided into flowering induction and flower organogenesis/formation. In the present study, we investigated how phytohormones affect the flowering process at different developmental stages. The results suggest that different hormones differentially affect flower induction and formation in saffron. The exogenous treatment of flowering competent corms with abscisic acid (ABA) suppressed both floral induction and flower formation, whereas some other hormones, like auxins (indole acetic acid, IAA) and gibberellic acid (GA), behaved contrarily at different developmental stages. IAA promoted flower induction, while GA suppressed it; however, GA promoted flower formation, whereas IAA suppressed it. Cytokinin (kinetin) treatment suggested its positive involvement in flower induction and flower formation. The expression analysis of floral integrator and homeotic genes suggests that ABA might suppress floral induction by suppressing the expression of the floral promoter (LFY, FT3) and promoting the expression of the floral repressor (SVP) gene. Additionally, ABA treatment also suppressed the expression of the floral homeotic genes responsible for flower formation. GA reduces the expression of flowering induction gene LFY, while IAA treatment upregulated its expression. In addition to these genes, a flowering repressor gene, TFL1-2, was also found to be downregulated in IAA treatment. Cytokinin promotes flowering induction by increasing the expression levels of the LFY gene and decreasing the TFL1-2 gene expression. Moreover, it improved flower organogenesis by increasing the expression of floral homeotic genes. Overall, the results suggest that hormones differently regulate flowering in saffron via regulating floral integrator and homeotic gene expression.